1993
DOI: 10.1182/blood.v82.3.1000.1000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hepatitis in patients receiving transfusions of blood components containing antibody to hepatitis C

Abstract: When hepatitis C virus antibody (anti-HCV) enzyme immunoassay (EIA1) testing became available in 1990, we tested samples from previously transfused blood units, traced the recipients of reactive units, and evaluated the recipients for HCV infection during the 12 months after transfusion. Ten of 42 recipients of EIA1-reactive blood were anti-HCV reactive on follow-up by EIA1 and 12 were reactive by a second- generation assay (EIA2). Reverse transcriptase-polymerase chain reaction (RT-PCR) detected HCV RNA in 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In this study, all of the traceable recipients of blood positive by RIBA 2 or PCR were found to have been infected with HCV. This contrasts with earlier studies using the first generation EIA and less rigorous confirmation methods, in which 40-93?40 of recipients were shown to have seroconverted (van der Poel et al, 1990;Kolho et al, 1992;Aoki et al, 1993). Our results suggest that virtually all recipients of blood shown to be HCV-positive by currently available immunoblot and PCR techniques will have seroconverted.…”
Section: Risk Of Hepatitis C 271contrasting
confidence: 99%
“…In this study, all of the traceable recipients of blood positive by RIBA 2 or PCR were found to have been infected with HCV. This contrasts with earlier studies using the first generation EIA and less rigorous confirmation methods, in which 40-93?40 of recipients were shown to have seroconverted (van der Poel et al, 1990;Kolho et al, 1992;Aoki et al, 1993). Our results suggest that virtually all recipients of blood shown to be HCV-positive by currently available immunoblot and PCR techniques will have seroconverted.…”
Section: Risk Of Hepatitis C 271contrasting
confidence: 99%
“… recognition that HCV EIA 1.0 identified a high proportion of the infected donors giving blood after initiation of HCV screening; concern over the effectiveness of general HCV lookback; and the ethical principle that patients have the right to know of a specific infectious exposure, even though the probability that the donors were infected may have been as low as 25 percent 6–8 …”
mentioning
confidence: 99%
“…Studies to date suggest that between 91 and 100% of transfusion recipients given blood collected from donors later found to be anti‐HCV positive will develop one or more markers for HCV ( Aoki et al ., 1993 ; Skaug et al ., 1993 ; Foberg et al ., 1996 ). However, caution should be exercised when comparing infectivity rates in these studies as variations may be due to differences in assay performance.…”
mentioning
confidence: 99%